FHIRbox, a cloud integration system for clinical observations - Alves, Nuno (2019)
With the recent technological developments new possibilities arise for the use of wearables and medical monitoring devices by patients and their respective integration into the digital health ecosystem. FHIRbox is a distributed system under development by the authors for integrating data from various diagnosis devices, complying with FHIR - the latest HL7 standard for exchanging clinical information. The innovative aspects of FHIRbox constitute a reference to drive a paradigm shift in terms of access to health information; as it is a solution that places the patient as the true owner of his clinical data. In this work the authors present the project requirements and the system architecture. Keywords: FHIRbox; HL 7; FHIR; health records; Health interoperability